2017
DOI: 10.3389/fendo.2017.00100
|View full text |Cite
|
Sign up to set email alerts
|

Medications Adherence and Associated Factors among Patients with Type 2 Diabetes Mellitus in the Gaza Strip, Palestine

Abstract: AimThe aim of this study was to evaluate the adherence to anti-diabetic medications among patients with type 2 diabetes mellitus (DM) seeking medical care in the Gaza Strip, Palestine.MethodsA cross-sectional study was conducted among 369 primary care patients with type 2 DM from October to December 2016. Adherence to medications was measured using the Morisky Medication Adherence Scale (MMAS-4). Socio-demographic and clinical variables, provider–patient relationship, health literacy, and health belief were ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
72
8
11

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(103 citation statements)
references
References 49 publications
12
72
8
11
Order By: Relevance
“…The present study revealed that levels of low, moderate, and high adherence to medication protocol amongst patients with diabetes were 27.2%, 59.2%, and 13.6%, respectively. These results differ from those of Elsous et al, who estimated 2.5%, 39.5%, and 58% of low, moderate, and high adherence to medication protocol [5,20]. These differences can be explained because adherence to medication is affected by many factors, including social and economic factors, attitudes, motivations and levels of physical/cognitive impairment of patients, severity of medical conditions, and the healthcare system in which the patient receives care.…”
Section: Discussioncontrasting
confidence: 72%
See 1 more Smart Citation
“…The present study revealed that levels of low, moderate, and high adherence to medication protocol amongst patients with diabetes were 27.2%, 59.2%, and 13.6%, respectively. These results differ from those of Elsous et al, who estimated 2.5%, 39.5%, and 58% of low, moderate, and high adherence to medication protocol [5,20]. These differences can be explained because adherence to medication is affected by many factors, including social and economic factors, attitudes, motivations and levels of physical/cognitive impairment of patients, severity of medical conditions, and the healthcare system in which the patient receives care.…”
Section: Discussioncontrasting
confidence: 72%
“…Medication adherence is an important determinant of therapeutic outcome such as glycemic indices and to prevent complications. According to data, adherence to medication varies from 10% to 74% in different populations [4,5]. Thus, this wide range might show barriers or influences of the related factors such as age, socioeconomic status, and disease duration on adherence to medication in people with diabetes.…”
Section: Introductionmentioning
confidence: 99%
“…has also found that increased duration of disease was associated with increased risk of non‐adherence to medications in patients with type 2 diabetes in Brazil. Another study reported that longer duration of disease was a predictor of medication non‐adherence in patients with diabetes in Gaza, but this association was not statistically significant …”
Section: Discussionmentioning
confidence: 95%
“…Another study reported that longer duration of disease was a predictor of medication non-adherence in patients with diabetes in Gaza, but this association was not statistically significant. [30] Patients with angina who have multiple comorbidities including dyslipidemia and hypertension usually need longterm management by multiple medications and complex medication regimens to control their conditions and prevent other complications, which could make medication adherence a complex task for such patients. [3,31] This association between number of chronic diseases and medication adherence was reported by the multiple regression analysis in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Two patients lacked some of their adherence data and were subsequently excluded from the analysis, leaving 251 patients for complete analysis. Pregnant patients and patients who were severely ill on the day of data collection were excluded from the sample as this is a common practice in such research [46]. In addition, excluded for logistical reasons such as the fact that they might not be in a position to sit for a period of time to complete the interview, in addition to their consultation time.…”
Section: Study Sample and Recruitmentmentioning
confidence: 99%